Self-reported depression and anxiety among COPD patients. A case-control study - Hurtado-Ruzza, Rafael; Álvarez-Calderón-Iglesias, Óscar; Becerro-de-Bengoa-Vallejo, Ricardo; Calvo-Lobo, César; San-Antolín, Marta; Losa-Iglesias, Marta Elena; Romero-Morales, Carlos; López-López, Daniel (São Paulo Medical Journal, 2022)
BACKGROUND: Anxiety and depression are the most prevalent mental disorders worldwide. However, the exact mechanisms linking chronic obstructive pulmonary disease (COPD) with depression and anxiety have not been identified. OBJECTIVES: To compare self-reported depression and anxiety among patients diagnosed with COPD in relation to healthy controls. DESIGN AND SETTING: Case control study at a public hospital institution in Spain. METHODS: We designed a case-control study. Patients were recruited using a consecutive sampling method from a single institution. Two groups were created: COPD and healthy controls. Data on medical history and demographic background were collected from the medical records. Self-reported depression levels were assessed using Beck’s depression inventory (BDI). Self-reported anxiety was measured using the State-trait anxiety inventory (STAI). RESULTS: Fifty-two patients with COPD and fifty healthy patients were included in this study. BDI scores were higher for COPD patients (10.23 ± 6.26) than in the control group (5.2 ± 6.56). STAI-state scores were higher for COPD patients (41.85 ± 12.55) than for controls (34.88 ± 9.25). STAI-trait scores were higher for COPD patients (41.42 ± 10.01) than for controls (34.62 ± 9.19). CONCLUSIONS: This study showed that there were higher levels of depression and anxiety among COPD patients than among healthy controls.